Memory strategies depending on interval of sequential memory presentation - Takase, Ryoken; Anada, Risa; Takase, Tomoki; Yokosawa, Koichi (Transactions of Japanese Society for Medical and Biological Engineering, 2020)
Working memory has slave systems called the phonological loop and the visual space sketch pad. In sequential memory tasks, in which working memory should play a role, memory performance is reduced by shortening the intervals between memory item presentations. To clarify how the working memory concerns the sequential memory, we recorded magnetoencephalograms from 29 subjects performing two sequential memory tasks with either long or short intervals (hereafter, slow and fast conditions, respectively). Amplitude of beta-band rhythm (14–29 Hz) was time-averaged during memory maintenance period. The averaged amplitude were compared between conditions in each 68 brain area. In inferior temporal gyrus (memory area) and lateral occipital cortex (visual area), the averaged amplitude of the fast condition was significantly larger than that of the slow condition. This result suggests that short interval of fast condition makes it difficult to recruit phonological loop, and recruits visual space sketch pad dominantly.